ANALYSIS OF CUSTOMER RELATIONSHIP MANAGEMENT AND SERVICE QUALITY TOWARDS CUSTOMER LOYALTY WITHCUSTOMER SATISFACTION AS AN INTERVENING VARIABLE AT PT. BADAK ICE DRINK FACTORY IN PEMATANG SIANTAR - Risma Nurhaini Munthe; Nurafrina Siregar; Erwansyah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This research aims to analyze the influence of Customer Relationship Management (CRM) and service quality on customer loyalty, with customer satisfaction as an intervening variable at PT. Badak Ice Drink Factory in Pematang Siantar. The study employs a quantitative research design, utilizing a survey to collect data from a sample of 190 respondents. Data analysis techniques include validity and reliability testing, as well as hypothesis testing using SmartPLS. The results reveal that CRM and service quality have a positive and significant effect on both customer satisfaction and customer loyalty. Furthermore, customer satisfaction mediates the relationship between CRM, service quality, and customer loyalty. These findings highlight the importance of implementing effective CRM strategies and providing high-quality service to enhance customer satisfaction and ultimately foster customer loyalty in the beverage industry.